The Profile of Family Farmers in the Regions of Brazil - Dias, Thyena Karen Magalhães; Khan, Ahmad Saeed; Costa, Edward Martins; Tabosa, Francisco José Silva; Castelar, Pablo Urano de Carvalho (Journal of Agricultural Studies, 2022)
Despite the importance of modernizing Brazilian agriculture through capitalization, alongside agricultural public policies, at the regional level this process has taken place asymmetrically and continues as such to this day. Thus, this work aims to verify the characteristics of family farmers and their establishments in the different regions of Brazil, based on municipal data from the 2017 Agricultural Census, using the Logit Multinomial econometric model. The results suggest heterogeneity among the different regions of the country, which corroborates the process of asymmetric modernization of Brazilian agriculture, and, through the econometric estimation, based on variations in the characteristics observed, the South region of Brazil has, in general, more favorable characteristics when compared to the other regions.